Chemical composition, biological activities, and quality standards of hawthorn leaves used in traditional Chinese medicine: a comprehensive review - Guo, Wenjing; Shao, Tingting; Peng, Yu; Wang, Haitao; Chen, Zhe-Sheng; Su, Haixiang (Frontiers in Pharmacology, 2023)
Hawthorn leaves also known as crataegi foilum, are a combination of botanical drugs used commonly in Traditional Chinese Medicine. Hawthorn, the plant from which hawthorn leaves are prepared, is distributed in Northeast China, North China, and other regions in China. Hawthorn leaves are known to activate blood circulation and eliminate stasis, invigorating Qi, eliminating turbidity, and reducing the levels of lipids. So far, over a hundred compounds have been isolated from hawthorn leaves, including flavonoids, terpenoids, lignans, organic acids, and nitrogenous compounds. Hawthorn leaves are used for the treatment of hypertension, protecting against ischemic injury, angina, hyperglycemia, hyperlipidemia, and certain other conditions. Several of the currently available clinical preparations also use hawthorn leaves as raw materials, such as Yixintong capsules, Xinan capsules, etc. The present report systematically reviews the chemical composition, biological activities, and quality standards of hawthorn leaves, to provide a scientific basis and reference for detailed research on hawthorn leaves.